Remote Power Using Android, PoE and VPN - Muhammad Amir Rozlan Bin Mohd Zamri; Munisamy, Sri Banu (Journal of Computing Technologies and Creative Content, 2020)
This final year project develops a simplified device that will replace the old tools to perform remote power. This project will help the worker to control the power of the device remotely from outside of the working area by using a VPN. The status of the power such as voltage, ampere, and watt provided by the controller is shown in an Android application. This project uses System Development Life Cycle (SDLC) model which is a prototype model as focusing on building, test, and then reworked when needed until an acceptable prototype is achieved. The result of the project should be the android application can perform remote power and notify the user of power failure.